Transition‐Metal π‐Ligation of a Tetrahalodiborane. Issue 2 (7th December 2017) - Braunschweig, Holger; Dewhurst, Rian D.; Jiménez‐Halla, J. Oscar C.; Matito, Eduard; Muessig, Jonas H.
Abstract: The reaction of tetraiododiborane (B2 I4 ) with trans ‐[Pt(BI2 )I(PCy3 )2 ] gives rise to the diplatinum(II) complex [{(Cy3 P)(I2 B)Pt}2 (μ2 :η 3 :η 3 ‐B2 I4 )], which is supported by a bridging diboranyl dianion ligand [B2 I4 ] 2− . This complex is the first transition‐metal complex of a diboranyl dianion, as well as the first example of intact coordination of a B2 X4 (X=halide) unit of any type to a metal center. Abstract : Million dollar BB : The reaction of tetraiododiborane with trans ‐[Pt(BI2 )I(PCy3 )2 ] gives rise to a diplatinum(II) complex supported by a bridging [B2 I4 ] unit. This complex is the first transition‐metal complex of a diboranyl dianion, as well as the first example of intact coordination of a B2 X4 (X=halide) unit of any type to a metal center.